2019
DOI: 10.1021/acs.iecr.9b03743
|View full text |Cite
|
Sign up to set email alerts
|

Methanol Aromatization over Mg–P-Modified [Zn,Al]ZSM-5 Zeolites for Efficient Coproduction of para-Xylene and Light Olefins

Abstract: In this work, a series of [Zn,Al]ZSM-5 zeolites was synthesized via isomorphous substitution using different Zn precursors, and the as-obtained zeolites were further subjected to Mg−P surface modification for efficient production of pxylene and light olefins (C 2 = ≈ C 4 = ) from methanol. The synthesized [Zn,Al]ZSM-5 zeolites are highly active in methanol to aromatics (MTA) reaction. Ascribed to the uniformly dispersed Zn species and greatly enhanced dehydro-cyclization reaction, [ZnS]ZSM-5 synthesized from Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…Ni et al followed a similar synthetic route to obtain nanosized Zn-modified ZSM-5 zeolite crystals to promote the yields of BTX (benzene, toluene, and xylene) in the methanol to aromatics (MTA) reaction . Other zinc precursors, such as ZnSO 4 , Zn­(AcO) 2 , and Zn­(NO 3 ) 2 , were also used in the preparation of Zn-modified ZSM-5 zeolite in the MTA reaction, and a similar promotion effect on aromatic selectivity was realized . These results together show the modification of ZSM-5 zeolite with Zn species via in situ hydrothermal synthesis, making the entry of Zn species into zeolite microporous channels easier compared to the traditional impregnation method.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Ni et al followed a similar synthetic route to obtain nanosized Zn-modified ZSM-5 zeolite crystals to promote the yields of BTX (benzene, toluene, and xylene) in the methanol to aromatics (MTA) reaction . Other zinc precursors, such as ZnSO 4 , Zn­(AcO) 2 , and Zn­(NO 3 ) 2 , were also used in the preparation of Zn-modified ZSM-5 zeolite in the MTA reaction, and a similar promotion effect on aromatic selectivity was realized . These results together show the modification of ZSM-5 zeolite with Zn species via in situ hydrothermal synthesis, making the entry of Zn species into zeolite microporous channels easier compared to the traditional impregnation method.…”
Section: Introductionmentioning
confidence: 90%
“…Su et al found that ZnOH + species in Zn-modified ZSM-5 zeolite are accounted for the formation of iso -alkanes in dimethyl ether to gasoline reaction . The formation of L acid sites (ZnOH + species) is determined by the location of Zn species (i.e., at the external surface or within the micropores) since it generated from B acid sites, and much attention has been focused on incorporating Zn species into zeolite micropores. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The light olefins are further developed into C 5+ non-aromatic hydrocarbons by polymerization and cyclization. Then the aromatics and alkanes are generated by hydrogen transfer and dehydro-cyclization reactions under the action of Brönsted acid sites [14,42]. The results of acidity measurement showed that the amount of the Brönsted acid sites decreased obviously after the doping of P, which was consist with the changes in the selectivity of aromatics and alkanes.…”
Section: Influence Of Phosphorus On the Catalytic Performancementioning
confidence: 99%
“…Firstly, the narrowed pore size made the generation of PX easier than that of other X isomers and C 9+ aromatics, and the small amount of other X isomers and C 9+ aromatics formed was also difficult to diffuse out the zeolite channel. Moreover, the isomerization reaction of PX was inhibited after PX diffusing to the external surface which was poisoned by P species [42]. Therefore, the P/HZSM-5 was highly shape-selective for PX in the MTA reaction.…”
Section: Influence Of Phosphorus On the Catalytic Performancementioning
confidence: 99%